Some Lithuanian ethnobotanical taxa: a linguistic view on Thorn Apple and related plants - Šeškauskaitė Daiva; Gliwa Bernd (BMC, 2006)
Abstract Background The perception and use of plants correspond with common plant names. The study of plant names may give insight into historical and recent use of plants. Methods Plant names in dictionaries and folklore have been evaluated. A etymological analysis of the names is provided. Onomasiological and semasiological aspects have been considered. Therefore, species named with names related to each other have been selected. Results Plant names containing the stem dag- or deg- may belong to either of two categories: incenses or thorny plants. Plants named in durn- have been in use as psychopharmaca. The name rymo points not to Rome but to the use of plants as anodyne or psychopharmaca.